Digital communications principles and systems - Otung, Ifiok (IET telecommunications series, 2014)
This book aims to provide post graduate students and practising engineers with a thorough understanding in the core principles and design issues of digital communications to meet the industry demand for in-depth expertise in digital transmission techniques. This book describes the engineering concepts and underlying physical considerations